A case of cooperation in the European OR education - Miranda, João; Nagy, Mariana (European journal of engineering education, 2011)
European cooperation is a relevant subject that contributes to building a competitive network of high education institutions. A case of teacher mobility on behalf of the Erasmus programme is presented: it considers some Operations Research topics and the development of the Lego on My Decision module. The module considers eight lecture hours in four sessions: (i) the introductory session, to focus on the basics of computational linear algebra, linear programming, integer programming, with computational support (Excel®); (ii) the interim session, to address modelling subjects in a drop by-session; (iii) the advanced session, on the sequence of (i), to consider uncertainty and also how to use multi-criteria decision-making methods; (iv) the final session, to perform the evaluation of learning outcomes. This cooperation at European level is further exploited, including curricula normalisation and adjustments, cultural exchanges and research lines sharing in the idea of promoting the mobility of students and faculty.